Is It Possible to Observe Society in Its Totality? Niklas Luhmann as Perseus and Medusa as Society - A. Yu. Antonovskiy (Социология власти)
The article raises the question of the theoretical and cognitive foundations of sociological observation in the system-communication theory of Niklas Luhmann. Observation of society in its entirety is possible only from within itself, and therefore its observer (sociologist, artist, writer, moralist, politician or participant in a social movement) is necessarily included in the observed object itself. This circumstance gives rise to the paradox of self-applicability or self-reference in their social specification, since generalizing statements about society, if they claim to be universal in description, are always applicable to the statements themselves. It is substantiated that the paradoxes of self- applicability and self-reference, without receiving their resolution, are never- theless performatively realized both in social reality itself and in its theoretical representation, and ensure the function of the social system — reflection of the system and the possibility of comparing one’s own observation resources with the methods of observation of adjacent communication systems. Following logic of self-observation, social theory is supplemented by a self-referential theoretical complex (sub-discipline), called “Self-Descriptions” (the fifth book of N. Luhmann’s fundamental work “Societies of Society”). This additional theory specializes in reconstructing the semantics of the concept of society, how society — in its communications, religion, mass media, art, politics, but today primarily in the optics of science — looked and looks at itself. Such inclu- sion of “Self-Description” (“shorthand”, “scene description”) in the corpus of social theory, as its integral and equal part with the function of describing the formation, semantics and theoretical resources of the theory of society itself, has become an important theoretical innovation in the field of social theory.